Germination response of buckwheat (Fagopyrum esculentum) grown in northern Patagonia at different temperatures. - Keil, Aldana Janet (2021)
Fil: Zubillaga, María Fany. Universidad Nacional de Rio Negro. CIT Rio Negro. Río Negro, Argentina.